Índice de confort de la vegetación (2008)
This article is a summary of the research project «Use ofBarranquilla´s Native Vegetation according to its Comfort Index», in which we analyze the environmental conditions created under the trees and, based on that, we came up witha comfort index that should be helpful for urban and architectural design, when selecting the species most likely to be used as a spatial component, given their climatic comfort potential.